2021
DOI: 10.1088/1742-6596/1865/4/042089
|View full text |Cite
|
Sign up to set email alerts
|

Research on MPPT Based on Gray Wolf Algorithm improved by Levy Flight

Abstract: In the late iteration of the gray wolf algorithm, the convergence results will have low accuracy becased of the elite retention.When implementing MPPT control, the maximum power point of the photovoltaic array cannot be accurately tracked, and it is easy to fall into the local optimum. Therefore, this paper proposes gray wolf algorithm improved with Levy flight applied to MPPT control. The algorithm introduces the Levy flight to search the head wolf position globally, then uses the group optimization of the gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…In the traditional WPA, the movement of the scout wolves during the wandering behavior primarily relies on the wandering step size step d a . [26][27][28] Based on the formula, it can be observed that the values of M d and m d are fixed in the given d dimensional space. Once the step size factor C is determined, the wandering step size remains constant throughout the iterations of the wolf pack.…”
Section: Improvement Of Wpa Algorithmmentioning
confidence: 99%
See 1 more Smart Citation
“…In the traditional WPA, the movement of the scout wolves during the wandering behavior primarily relies on the wandering step size step d a . [26][27][28] Based on the formula, it can be observed that the values of M d and m d are fixed in the given d dimensional space. Once the step size factor C is determined, the wandering step size remains constant throughout the iterations of the wolf pack.…”
Section: Improvement Of Wpa Algorithmmentioning
confidence: 99%
“…In the traditional WPA, the movement of the scout wolves during the wandering behavior primarily relies on the wandering step size stepad$$ {\mathrm{step}}_a^d $$ 26–28 . Based on the formula, it can be observed that the values of Md$$ {M}_d $$ and md$$ {m}_d $$ are fixed in the given d$$ d $$ dimensional space.…”
Section: Algorithms and Their Fusion Strategiesmentioning
confidence: 99%
“…In conformity with the coercivity H c , the maximum value of the magnetization M T IP , the maximum value of the external magnetic field is H T IP . In line with (18), the bound of parameter α is traversed with a certain step size, and then the bound of parameter a is calculated based on the values of k 1 and k max according to (17) and (26). Figure 3 illustrates the detailed procedure.…”
Section: The Bounds For Parameters Of J-a Modelmentioning
confidence: 99%